A Quiropraxia na construção da saúde coletiva: a visão dos quiropraxistas - Santos, Thiana Paula Schmidt dos (Universidade do Vale do Rio do Sinos, 2008)
The present research study aimed at verifying, through interviews carried out with chiropractors, what their concept of collective health is; the relationship between collective health and chiropractic, as well as possible areas in collective health in which chiropractors can be engaged in. This is an exploratory research with a qualitative approach carried out through content analysis. Fifteen chiropractors who had been practicing for a minimum of two years in the Porto Alegre Metropolitan area, in the Sinos Valley and Mountains region in Southern Brazil, participated on the research. The data was collected in July 2008, by the use of a semi-structured interview. A good concept of what collective health is was verified among the chiropractors. They were also able to establish an important relationship between collective health and chiropractic, mainly related to preventive and educational measures, as well as to envision several possible areas in which chiropractors can engage in regarding collective health,
Keywords: conhecimento; saúde coletiva; quiropraxia; knowledge; public health; chiropractic; Ciências da Saúde